STUDI KOMPARASI HIDROGRAF SATUAN SINTETIK GAMA I DAN HIDROGRAF SATUAN ALAMI SUB DAS GARANG - , GILANGTRIATAMA ARDINANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Analysis of hydrological sciences in studying the phenomenon on earth is needed in particular the phenomenon of flooding. In the hydrological science, flood phenomenon is associated with the flow of the river. Hydrologic methods to analyze streamflow for flood estimation called unit hydrograph. However, the AWLR data recording, measurement data and also the data flow of the continuous rain is not always there for each area to be examined, so that the method of flooding estimation had been developed, its called synthetic unit hydrograph. One of the methods and models that have been developed to assist in the analysis of hydrologic conditions in the watershed is GAMA I synthetic unit hydrograph. The purpose of this study was to assess the natural unit hydrograph in the study area, reviewing GAMA I synthetic unit hydrograph in the study area and to find out how much accuracy and deviations of GAMA I synthetic unit hydrograph against natural unit hydrograph. The research was done by comparing the unit hydrograph established by watershed morphometric parameters (GAMA I) with the hydrograph formed according to the data flow and rainfall data (Natural Unit Hydrograph) in Garang sub-watershed then make observation unit hydrograph according to the study area. Comparisons were made with a look for deviation values beetwen GAMA I and natural unit hidrograph. Garang Sub-watershed natural unit hidrograph has a value of Qp 3.73 m3/sec